The role of salinity and brine ions in interfacial tension reduction while using surfactant for enhanced oil recovery - Hosseini, S.N. (Maxwell Science Publications, 2015)
The reduction of IFT through application of surfactant is one of the widely known Enhanced Oil Recovery (EOR) methods in the petroleum industry. However, not much is known about the role of brine ions during this process. Thus, this study focuses on the capability of reducing IFT through salt ions in aqueous phase while using cationic surfactant. To determine the conditions required to reduce IFT between Brine Surfactant Solution (BSS) and oil. Experiments were carried out on a given sample of crude oil and carbonate rock slices. Dodecyl Trimethyl Ammonium Bromide (DTAB) was used as Cationic surfactant and effect of different concentrations of Ca+2, Mg+2were investigated. Concentrations of Ca+2, Mg+2were changed in range of (0.015-0.07 Wt ) while concentrations of other ions were kept constant. All experiments were carried out at 35Â°C. Results show that these divalent ions and their concentrations have significant influence on IFT. The IFT is in direct proportion to the salinity, that is, with rise in salinity, IFT increases significantly. An increase in concentration of divalent cations Ca+2and Mg+2causes a decrease in IFT between crude oil and BSS. However, strong effects on IFT are observed for Ca2+relatively to Mg+2under constant concentration of DTAB and same temperature. Â© Maxwell Scientific Organization, 2015.